Praia da Estação: carnavalização e performatividade - Thalita Motta Melo (2014)
This work investigates the borders and crossroads between Art / Life / Politics from Praia da Estação performing experiences, Belo Horizonte, and its developments and crossings, as well as the global and local levels, always in transit, sometimes indiscernible. As fundamental axes, were permeated notions of Carnivalization, supported by the theory of Mikhail Bakhtin, and the Performativity, based on studies of Erika Fischer-Lichte, investigating in both notions, the body-on-party collective power as aesthetic transforming the urban landscape. The research also discusses, going through the deepest layers of Praia da Estação on the various faces of spectacularization of the city and its consequences, such as privatization of public space, gentrification, hygienism, non-places, among many other possible folds, reducing the body experience in the city.